Population genomics of yams: evolution and domestication of Dioscorea species - Sugihara, Y.; Kudoh, A.; Oli, M.T.; Takagi, H.; Natsume, S.; Shimizu, M.; Abe, A.; Asiedu, R.; Asfaw, A.; Adebola, P.O.; Terauchi, R. (Springer, 2021)
Yam is a collective name of tuber crops belonging to the genus Dioscorea. Yam is important not only as a staple food crop but also as an integral component of society and culture of the millions of people who depend on it. However, due to its regional importance, yam has long been regarded as an “orphan crop” lacking a due global attention. Although this perception is changing with recent advances in genomics technologies, domestication processes of most yam species are still ambiguous. This is mainly due to the complicated evolutionary history of Dioscorea species caused by frequent hybridization and polyploidization, which is possibly caused by dioecy that imposed obligate outcrossing to the species of Dioscorea. In this chapter, we provide an overview of the evolution of Dioscorea and address the domestication of yam from population genomics perspectives by focusing on the processes of hybridization and polyploidization. A review is given to the recent population genomics studies on the hybrid origin of D. rotundata in West and Central Africa, the global dispersion of D. alata through human migrations, and the whole-genome duplication of the South America species of D. trifida. In the end, we give a summary of current understanding of sex-determination system in Dioscorea.